Предмет: Алгебра,
автор: tanyatimchenko
Помогите решить
разложите на множители
3х*в квадрате* +12ху+12у*в квадрате*
8а(b-3)+c(3-b)
х*в квадрате* +3х-2ху-6у
решите уравнение
(х-1)(х*в квадрате*+х+1)-х*в квадрате*(х-1)=0
Ответы
Автор ответа:
0
Итак. Рока только 1
3х^2+6ху+6ху+12у^2=3х(х+2у)+6у(х+2у)=(3х+6у)(х+2у)
3х^2+6ху+6ху+12у^2=3х(х+2у)+6у(х+2у)=(3х+6у)(х+2у)
Автор ответа:
0
(8а-с)(b-3)
Похожие вопросы
Предмет: Другие предметы,
автор: LemonkaUwU
Предмет: Биология,
автор: ivashkoanna5
Предмет: Математика,
автор: ainakrassa
Предмет: Алгебра,
автор: elya1205